Miracles and Machines : A Sixteenth-Century Automaton and Its Legend - King, Elizabeth, 1950-; Todd, W. David (Book collections on Project MUSE., 2023)
"This richly illustrated volume tells the uncanny story of a sixteenth-century automaton and the legend that has grown up around it"--